Microstructure and composition evolution of He charged solid-gas nanocomposite films of different matrix elements during thermal annealing in vacuum - Asunción Fernández; M. Carmen Jiménez de Haro; Dirk Hufschmidt; Olga Montes; Thierry Sauvage; F. Javier Ferrer; Amaël Caillard; Pascal Brault; Anne-Lise Thomann (Scientific Reports)
Abstract Sputtering of cobalt, silicon and zirconium in a helium magnetron discharge (MS) is reported as a bottom-up procedure to obtain He-charged films (i.e. 4He and 3He filled nanopores encapsulated in the matrix material). Composition and microstructural analyses are presented from ion beam analysis (IBA) and scanning and transmission electron microscopies (SEM and TEM). Helium desorption was investigated by IBA in a dedicated chamber for “in situ” thermal evolution in vacuum. The simultaneous recording of the helium and matrix-element signals shows different behaviors of the different matrix elements (i.e. Co, Si and Zr) and deposition conditions (i.e., DC or RF discharge modes and dynamic or quasistatic vacuum). Effusion, blistering, delamination and flaking have been observed for the different samples leading to the formation of nano-porous/nanostructured thin films. The methodology is being envisaged as a process for nanostructured thin-films fabrication with potential applications.